2023
DOI: 10.3390/genes14010222
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Landscape of SOX Genes to Inform Genotype-to-Phenotype Relationships

Abstract: The SOX transcription factor family is pivotal in controlling aspects of development. To identify genotype–phenotype relationships of SOX proteins, we performed a non-biased study of SOX using 1890 open-reading frame and 6667 amino acid sequences in combination with structural dynamics to interpret 3999 gnomAD, 485 ClinVar, 1174 Geno2MP, and 4313 COSMIC human variants. We identified, within the HMG(High Mobility Group)- box, twenty-seven amino acids with changes in multiple SOX proteins annotated to clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Thus, it has become common that gene therapies are initiated only in individuals that have either a variant that occurs in multiple individuals (often autosomal recessive conditions) or the variant results in a frameshift or nonsense change that removes large chunks of protein observed to be removed in other patients with the disorder. There is a need for characterizing VUSs rapidly using existing data [ 23 , 64 , 65 , 66 , 67 , 68 ], high-throughput wet lab techniques used in NAA10 characterizations [ 69 ], knowledge from paralog proteins such as the work on SOX transcription factors [ 70 ], or through crowd-sourcing variant lists to identify matching variant locations and phenotypes as was the case for MED13 [ 71 ].…”
Section: Biological Considerationsmentioning
confidence: 99%
“…Thus, it has become common that gene therapies are initiated only in individuals that have either a variant that occurs in multiple individuals (often autosomal recessive conditions) or the variant results in a frameshift or nonsense change that removes large chunks of protein observed to be removed in other patients with the disorder. There is a need for characterizing VUSs rapidly using existing data [ 23 , 64 , 65 , 66 , 67 , 68 ], high-throughput wet lab techniques used in NAA10 characterizations [ 69 ], knowledge from paralog proteins such as the work on SOX transcription factors [ 70 ], or through crowd-sourcing variant lists to identify matching variant locations and phenotypes as was the case for MED13 [ 71 ].…”
Section: Biological Considerationsmentioning
confidence: 99%
“…These TFs influence cell differentiation, proliferation, migration, invasion, and metastasis in several tumor types [15][16][17][18][19][20]. The pleiotropic nature of SOX proteins is underscored by their ability to regulate different gene sets in diverse cellular contexts and tissues [9,21]. Adding to the complexity of cancer research is the variability observed in tumor types, genetic mutations, tumor locations, stages, patient characteristics, treatment responses, and drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…These TFs influence cell differentiation, proliferation, migration, invasion, and metastasis in several tumor types [ 16 , 17 , 18 , 19 , 20 , 21 ]. The pleiotropic nature of SOX proteins is underscored by their ability to regulate different gene sets in diverse cellular contexts and tissues [ 14 , 22 ]. The complexity of cancer research is compounded by the diversity observed across tumor types, genetic mutations, tumor sites, stages, patient characteristics, treatment responses and outcomes, further challenging the oncology field.…”
Section: Introductionmentioning
confidence: 99%